Pengaruh Ukuran Perusahaan, Capital Intensity Dan Inventory Intensity Terhadap Tax Avoidance (Studi Empiris Pada Sub Sektor Food And Baverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2024) - Muhammad Ravi Sayid Fareza; Rahmat Kurniawan (CV. ITTC INDONESIA, 2025)
This study examines the effect of firm size, capital intensity, and inventory intensity on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Tax avoidance is considered a legal strategy to minimize tax burdens by exploiting regulatory loopholes. Using purposive sampling, 126 firm-year observations were obtained, and the data were analyzed using multiple linear regression via IBM SPSS 25. The results show that firm size and capital intensity have a positive and significant effect on tax avoidance, indicating that larger firms with greater fixed asset investment possess stronger capacity and flexibility in undertaking aggressive tax planning. Conversely, inventory intensity has no significant effect on tax avoidance, suggesting that inventory-based investment does not determine tax avoidance practices. These findings emphasize the need for stricter fiscal oversight on large and high-capital firms due to their higher propensity for tax avoidance.